MICROPROPAGATION OF AN ENDANGERED AND ENDEMIC MEDICINAL PLANT CAYRATIA PEDATA VAR. GLABRA - S, SHARMILA; EK, RAMYA; S, MOWNIKA; SM, DHIVYA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the present study was to develop standardization protocol for the successful in vitro mass propagation of Cayratia pedata var. glabra through leaf and stem explants, since it is a rare, endangered, and endemic medicinal plant using biotechnological involvements and to conserve this endangered species. Methods: The application of biotechnological principles for the establishment of micropropagation under in vitro conditions has been studied by following the methods. The explants, namely, leaf and stem harvested from in vivo plants were thoroughly washed and properly sterilized with sterilients. The explants were transferred to Murashige and Skoog (MS) medium supplemented with growth regulators 6-benzyladenine (BAP) and naphthalene acetic acid (NAA) in the concentration range of 0.5–3.0 mg/l which were tested for callus induction and morphogenesis. The elongated shoots were transferred to MS medium supplemented with NAA at different concentrations for root induction. Results: The explants collected from the field (shola) were treated in different steriliants with various concentrations at different time for sterilization. Among the various combinations tried, the Teepol treatment for 10 min followed by bavistin 20 min, antibiotics, namely, ampicillin and rifampicin for 20 min, 70% alcohol for 30 s, and 0.12 % HgCl2 for 3 min was found to be effective. The explants were cultured in MS medium supplemented with various concentrations of BAP and NAA. The results noted that an increase in the concentration of BAP concomitantly reduced the frequency of callus formation. The maximum callusing frequency and more number of shoot formation was observed in the lower concentration of BAP (0.5 mg/l) in combination with NAA (0.2 mg/l). The callus obtained from all the above combinations was sub-cultured on MS medium with same combinations of BAP and NAA. The maximum frequency of root formation in leaf callus was 85% and 75% in stem callus and both were achieved on MS medium with NAA (1 mg/l) after 2 weeks. Conclusions: The current investigation provides a competent in vitro propagation method for C. pedata var. glabra which could be commercialized for developing identical plants with high-quality mass multiplication rate and for better conservation of the germplasm. Both the methods described here are well suited for the mass multiplication of this critically endangered and endemic climber species.